Evaluation of the functional properties of the quinoa protein isolate (Chenopodium quinoa Willd) INIAP-TUNKAHUAN variety with potential use in human nutrition - Lozano, Richy (2019)
Background: Quinoa is a gluten-free food has high potential in human nutrition, due to its high nutritional value, high protein quality, whose functional properties are ideal for development of new food products with high added value; however, these properties can be lost during processing Objective: To evaluate the effect of two protein extraction procedures (with and without the removal of phenolic compounds) on the functional properties of protein isolates obtained from the quinoa flour INIAP Tunkahuan variety. Methods: Isolation of quinoa proteins was performed by solubilization at alkaline pH (9.0) / isoelectric precipitation at acidic pH (5.0). The removal of phenolic compounds was carried out with an acid treatment (pH 4.5) prior to the extraction of their proteins. The technological potential in the lyophilized isolate was evaluated through functional properties. Results: The removal of compounds significantly affected the color of the protein isolate, making it darker, also caused a decrease in the amount of protein extracted, in its water retention capacity and in its emulsifying property, while the foaming capacity was independent of procedure used. Finally, a higher viscosity was observed in the protein isolate obtained without removal of phenolic compounds. Conclusion: Quinoa proteins can be a promising ingredient in the production of functional foods, but studies need to continue on the bioactive properties of their peptides.